2023
DOI: 10.3390/nu15040979
|View full text |Cite
|
Sign up to set email alerts
|

The Associations of Birthweight for Gestational Age Status with Its Differential 0–2 Year Growth Trajectory and Blood Pressure at Two Years of Age in Chinese Boys and Girls

Abstract: The first 1000 days of life represents a critical period for lifelong metabolic health. This study prospectively examined the contrasts between the growth trajectories of large, small, and appropriate sizes for gestational age (LGA, SGA, and AGA) term-born infants in their first two years, and their blood pressure at two years. In 2012–2013, 806 Chinese mother-newborn dyads were enrolled in the Shanghai Obesity and Allergy Birth Cohort Study. Repeated anthropometric measures were obtained at age 42 days, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
5
0
4
Order By: Relevance
“…Another study among children with OWO (mean age 11.8 years) also reported that, compared to being born appropriate for gestational age (AGA), SGA was associated with a higher risk of hypertensive BP and low HDL, while large for gestational age (LGA) was associated with a lower risk of hypertensive BP [25]. Our recent study likewise showed that SGA was associated with higher SBP, and LGA with lower DBP at two years of age in boys, though not in girls, adjusting for child current ZWFL [17]. This can be explained by the capacityload mode, where birth weight is a marker of capacity and childhood BMI or skinfolds are markers of load [6].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Another study among children with OWO (mean age 11.8 years) also reported that, compared to being born appropriate for gestational age (AGA), SGA was associated with a higher risk of hypertensive BP and low HDL, while large for gestational age (LGA) was associated with a lower risk of hypertensive BP [25]. Our recent study likewise showed that SGA was associated with higher SBP, and LGA with lower DBP at two years of age in boys, though not in girls, adjusting for child current ZWFL [17]. This can be explained by the capacityload mode, where birth weight is a marker of capacity and childhood BMI or skinfolds are markers of load [6].…”
Section: Discussionmentioning
confidence: 66%
“…Higher birth weight was associated with higher child weight measures (for example, BMIZ or ZWFL), and SGA was associated with lower child weight measure at ages of 2, 4, and 7 years [17,23]. However, birth weight has been negatively associated with SBP at the age of 4 years and lower SBP and DBP at the age of 7 years [23].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Женщины с избыточным весом и ожирением имеют повышенный риск гестационного сахарного диабета (СД), гипертензивных расстройств, плацентарных нарушений, задержки роста плода и фетальной макросомии. В последующем разные постнатальные траектории массо-ростовых показателей компенсируют как внутриутробное ограничение, так и избыточный рост плода [2,8]. У крупновесных младенцев в первые годы после рождения отмечается снижение темпов прироста антропометрических показателей.…”
Section:  введениеunclassified
“…Женщины с избыточным весом и ожирением имеют повышенный риск гестационного сахарного диабета (ГСД), гипертензивных расстройств, плацентарных нарушений, задержки роста плода и фетальной макросомии. В последующем разные постнатальные траектории массо-ростовых показателей компенсируют как внутриутробное ограничение, так и избыточный рост плода [2,7]. У большинства детей, рожденных маловесными, наблюдается догоняющий рост, а у младенцев, рожденных крупновесными, в первые годы жизни наблюдается снижение темпов прироста антропометрических показателей.…”
Section:  введениеunclassified